2021
DOI: 10.1097/md.0000000000026246
|View full text |Cite
|
Sign up to set email alerts
|

Predicting ventilator-associated pneumonia with machine learning

Abstract: Ventilator-associated pneumonia (VAP) is the most common and fatal nosocomial infection in intensive care units (ICUs). Existing methods for identifying VAP display low accuracy, and their use may delay antimicrobial therapy. VAP diagnostics derived from machine learning (ML) methods that utilize electronic health record (EHR) data have not yet been explored. The objective of this study is to compare the performance of a variety of ML models trained to predict whether VAP will be diagnosed during the patient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…The BRT algorithm was derived from an ensemble machine learning method, which was proved e ciently in dealing with non-linear relationships and interaction between covariates [37] and had been widely used for diseases risk explanation and prediction, including avian in uenza [38], Middle East respiratory syndrome coronavirus [17] and scrub typhus [39]. Machine learning has been proven increasingly integrated into clinical practice, with applications ranging from pre-clinical data processing, bedside diagnosis assistance, patient strati cation, treatment decision-making, and early warning as part of primary and secondary prevention, which has been widely used for risk factors investigation and prognostic prediction [40], including VAP diagnostics [41] and prognosis [42].…”
Section: Discussionmentioning
confidence: 99%
“…The BRT algorithm was derived from an ensemble machine learning method, which was proved e ciently in dealing with non-linear relationships and interaction between covariates [37] and had been widely used for diseases risk explanation and prediction, including avian in uenza [38], Middle East respiratory syndrome coronavirus [17] and scrub typhus [39]. Machine learning has been proven increasingly integrated into clinical practice, with applications ranging from pre-clinical data processing, bedside diagnosis assistance, patient strati cation, treatment decision-making, and early warning as part of primary and secondary prevention, which has been widely used for risk factors investigation and prognostic prediction [40], including VAP diagnostics [41] and prognosis [42].…”
Section: Discussionmentioning
confidence: 99%
“…Successive iterations of trees use gradient descent on the prior trees to minimize the error of the next tree that was formed. XGBoosting has been shown to exhibit excellent performance for a wide range of classification problems in acute and chronic conditions [ 44 - 48 ]. For comparison with the structurally complex XGBoosting model, logistic regression and multilayered perceptron models were also trained and tested.…”
Section: Methodsmentioning
confidence: 99%
“…A significant number of AI/machine learning models have been developed that try to predict the occurrence of an event in advance, commonly termed 'forecasting' . Ventilator associated pneumonia (VAP), central-line associated blood stream infections (CLABSI), as well as the risk of colonization/infection with a multidrug resistant pathogen (MDR) are just a few examples for which prediction models have been developed [5][6][7][8]. The forecasting of sepsis and/or septic shock has, however, dominated this domain, as illustrated by the no more than 15 retrospective papers and 1 prospective interventional study carried out solely in the ICU that were identified by Fleuren et al in their recent systematic review [9].…”
Section: Predicting Infectionmentioning
confidence: 99%